2020
DOI: 10.1101/2020.08.01.230672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution of plasmid fitness effects explains plasmid persistence in bacterial communities

Abstract: Plasmid persistence in bacterial populations is strongly influenced by the fitness effects associated with plasmid carriage. However, plasmid fitness effects in wild-type bacterial hosts remain largely unexplored. In this study, we determined the distribution of fitness effects (DFE) for the major antibiotic resistance plasmid pOXA-48 in wild-type, ecologically compatible enterobacterial isolates from the human gut microbiota. Our results show that although pOXA-48 produced an overall reduction in bacterial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 90 publications
(92 reference statements)
2
23
0
Order By: Relevance
“…However, our data are consistent with those of another recent study that tested the fitness effect of a given plasmid across the range of genetic backgrounds present in a host species. Like ours, this study revealed diverse fitness impacts ranging across a continuum from costly to beneficial (Alonso-del Valle et al, 2020). These data highlight that the fitness effects of a plasmid can be highly strain-specific, and thus are likely to arise from specific genetic interactions rather than the generic biosynthetic costs of plasmid maintenance.…”
Section: Discussionsupporting
confidence: 65%
“…However, our data are consistent with those of another recent study that tested the fitness effect of a given plasmid across the range of genetic backgrounds present in a host species. Like ours, this study revealed diverse fitness impacts ranging across a continuum from costly to beneficial (Alonso-del Valle et al, 2020). These data highlight that the fitness effects of a plasmid can be highly strain-specific, and thus are likely to arise from specific genetic interactions rather than the generic biosynthetic costs of plasmid maintenance.…”
Section: Discussionsupporting
confidence: 65%
“…We performed control experiments mimicking the growth conditions of the competition experiments to ensure that plasmid loss in plasmid-carrying strains is negligible. Moreover, previous results indicated that plasmid conjugation under the experimental conditions used for the competition assays do not significantly affect relative fitness determinations (Alonso-del Valle et al, 2020).…”
Section: Competition Assaysmentioning
confidence: 96%
“…The clinical E. coli strains used in this study were isolated during the R-GNOSIS project, which included representative ESBL-producing enterobacteria from hospitalized patients in the Ramon y Cajal University Hospital during a 2 year period (Hernández-García et al, 2018b;León-Sampedro et al, 2020). The E. coli strains used here, and their corresponding transconjugants, were described and characterized previously (Alonso-del Valle et al, 2020) and Supplementary file 1D).…”
Section: Bacterial Strains Plasmids and Culture Conditionsmentioning
confidence: 99%
“…They also used a system of differential equations describing the interactive change of the components population density, antibiotic concentration ( -lactam), nutrient level and Bla concentration ( -lactamase). Valle et al [109] studied the distribution of plasmid fitness effects for the major antibiotic resistance plasmid pOXA-48. They found this to be dominated by quasi-neutral effects, which, incorporated in a simple system of ordinary differential equations, indicated that plasmid stability increases with bacterial diversity and is less dependent on conjugation.…”
Section: Modeling Approachesmentioning
confidence: 99%